Formulasi Islamic Buy Now Pay Later (BNPL) untuk Mencapai Demokratisasi Ekonomi Syariah - Prawitra Thalib; Fahrian Saleh Siregar; Wimboko Wimboko; Ibtisam @ Ilyana Ilias; Angelica Milano Aryani Wibisono (Syariah: Jurnal Hukum dan Pemikiran, 2025)
The rapid growth of financial technology has reshaped global economic structures and accelerated the diffusion of Buy Now, Pay Later (BNPL) schemes, which commonly rely on interest‑based deferred payments. In Muslim‑majority jurisdictions such as Indonesia, this raises controversy over the permissibility of BNPL, given its riba‑like charges and opaque fee structures, alongside a regulatory gap that has not yet been addressed through a dedicated Islamic BNPL framework. This article examines that gap by asking, first, how a Sharia‑compliant BNPL model can be normatively formulated? and second, how such a model can contribute to achieving Sharia economic democracy? Using normative legal research based on historical and systematic interpretation, and employing conceptual, statute, and comparative approaches, the study analyses BNPL regulation and practice in Qatar, Malaysia, and Indonesia. The findings show that current Indonesian BNPL products embed riba, gharar, and unjust enrichment, whereas Qatar and Malaysia have begun to redesign BNPL through Murabaha, Ijarah, and Qard contracts under explicit Sharia governance and consumer‑protection rules. The study then proposes a legal‑contractual model for Islamic BNPL that combines fixed‑price or cost‑based fees, transparent contractual disclosure, capped non‑profit penalties, and formal Sharia supervision, operationalised through indicators of access, affordability, transparency, anti‑exploitation, and ethical governance. The article concludes by recommending that Indonesian regulators adopt a specific Islamic BNPL act, integrate Islamic supervisory mechanisms, and standardise consumer‑protection safeguards so that Islamic BNPL can function as an instrument of inclusive finance and Sharia‑based economic democracy.